Model Desain Multimedia Pembelajaran - Eny Munisah (Edukasi Lingua Sastra, 2019)
Multimedia learning is a combination between text, picture, chart, animation, and audiovisual. It’s given by interactive ways, so it can make a learning experience for the students as their daily life. Multimedia is very important right now, because it made to complete each other, so that the entire system is effective, the whole is greater than the sum of its parts. Multimedia also gives stimulus for training and learning in outdoor. The designs are text, picture, animation, and sound by six stages, they are: (1) analyze learners, (2) state objectives, (3) select methods, (4) utilize media, (5) require learner participation, (6) evaluate and revise.